Stunting Prevention Education with Nutrition Counseling and Provision of Nutritional Food at Rantauprapat City Community Health Center, Labuhanbatu Regency - Harahap, Halimah Tusakdiyah; Elliana, Agusta Dian (International Journal of Community Service (IJCS), 2025)
This Study to ensure that every mother and toddler gets the right access and necessary health information, thereby reducing the risk of stunting and other health problems that can affect their growth and development. Using a qualitative approach, the study examines stunting. Community Service Activities on stunting prevention education by providing nutritional counseling and providing food and examining the nutritional status of toddlers were carried out on March 22, 2025 at the Rantauprapat City Health Center . This activity has increased the knowledge of the target audience. Increasing the knowledge of mothers of toddlers about balanced nutrition in toddlers is expected to improve the attitudes and actions of mothers in providing balanced nutrition to toddlers so that the nutritional status of toddlers is in the normal category. This activity can make a positive contribution in reducing and preventing nutritional problems in Indonesia, especially in the Rantauprapat City Health Center area, Labuhanbatu Regency.